Revolusi Diksi: Pergeseran Ideologi Robin Swift Dalam Novel Babel (Kajian Stilistika) - Atikah Putri, Rismaya (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
The ideological transformation of Robin Swift as the main character of Babel is the main axis of the story’s development. In literary work, especially novels, ideology transformation and character development are reflected through linguistic aspects used in the narration, both from the character’s dialogue and the author’s narration. This research aims to uncover how diction used to reflect ideology transformation and also to complement previous studies. This research uses the descriptive qualitative method with a stylistic approach to examine the diction choice and its meaning in Babel: Or the Necessity of Violence: An Arcane History of the Oxford Translators’ Revolution by R.F. Kuang. The data was collected using the purposive sampling technique in line with themes such as resistance and violence and the character’s views on authority. Furthermore, note-taking techniques were used to collect quotes from Robin's dialogues and monologues that met with the criteria. The data was then analyzed by identifying the choice of dictions and styles, then interpreting its meaning and stylistic function. Research findings show that Robin’s ideological transformation is represented through metaphors, repetitions, anaphora, hyperbole, irony, rhetorical questions, euphemisms, and dysphemisms with various associations and connotations. During the naïve phase, Robin tends to use dictions with positive connotations to describe authority and dictions with defection meaning and feelings of fear and denial for his rebellion. In contrast, in the revolution phase towards the end of the story, Robin used radical, violent diction that has negative connotations and is full of hatred toward the ruling authorities.